Scientific Article Writing Training For Special Education Teachers At Slb Buah Hati, Jambi City - Ariyani , Rika (Jurnal Masyarakat Mengabdi, 2025)
This scientific article writing training was motivated by the limited ability of special education (SLB) teachers to document their teaching experiences and practices in the form of scholarly writing. In fact, the publication of scientific work is one of the indicators of teacher professionalism and a key component of continuous professional development. This community service activity aimed to enhance the understanding and skills of SLB Buah Hati teachers in Jambi City in writing scientific articles suitable for publication in academic journals. The partner institution for this activity was SLB Buah Hati, located in Jambi City, with a total of 14 participating teachers. The methods of implementation included lectures, discussions, and hands-on writing practice based on each participant’s teaching experience. The results showed an improvement in participants’ understanding of scientific article structure, citation and bibliography writing techniques, and academic paragraph development. Quantitatively, 10 out of 14 participants were able to complete a draft of a basic scientific article, ready for further editing and potential journal submission. This program proved to be effective in raising awareness and building foundational competencies among SLB teachers in scientific writing as a means of contributing to the development of inclusive education.